Ban the Box: Outcomes of Mandatory Disclosure and Predictors of Voluntary Disclosure of Criminal History in Job Applications - Scherini, Ginevra Marta (2018)
The present study was conducted in order to examine the outcomes of mandatory disclosure of criminal history on the individual during the job application process and predictors of the likelihood of voluntary disclosure. It was hypothesized that having to disclose criminal history would predict higher levels of self-identification with criminal history, higher levels of experienced discrimination, higher levels of perceived stigma, lower levels of attraction towards the organization, lower confidence in obtaining employment, and lower levels of likelihood of voluntary disclosure. It was also hypothesized that environmental support, employment self-efficacy, self-identification with criminal history, and less experienced discrimination would predict a higher likelihood of voluntary disclosure. Using linear regression analyses and data obtained by surveying 150 participants with prior convictions, results showed that only identifying with criminal history predicted the likelihood of disclosure, and that having to disclose predicted higher levels of experienced discrimination, a lower likelihood of voluntary disclosure, and lower levels of employer attractiveness. These findings provide support to past findings showing that Ban the Box policies have positive outcomes towards the reintegration of ex-offenders, and furthermore, that by not forcing applicants to disclose their criminal history, ex-offenders are more likely to voluntarily disclose and have a better perception of their potential future employers